International Perspectives on Water Quality Management and Pollutant Control - Quinn, Nigel W.T (IntechOpen, 2013)
The level of surface water quality protection is variable around the world in large part due to the relative effectiveness of environmental regulation and the degree to which science influences the regulatory process. In the United States, at the federal level, the Total Maximum Daily Load (TMDL) has been an effective policy and water quality management tool for dealing with both point source and non-point source pollution. The TMDL provides a rational framework for estimating the assimilative capacity of the receiving water body for certain contaminants and applying factors of safety and incorporating acceptable levels of water quality criteria violation - provided the local stakeholders have a say in the decision making process. This collection of articles from around the world are good examples of the application of sound scientific principles to solve pressing water quality problems.